2012
DOI: 10.2174/1874325001206010129
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Tennis Elbow Release Under Local Anaesthesia

Abstract: Introduction:When the non-operative treatment of tennis elbow fails to improve the symptoms a surgical procedure can be performed. Many different techniques are available. The percutaneous release of the common extensor origin was first presented by Loose at a meeting in 1962. Despite the simplicity of the operation and its effectiveness in relieving pain with minimal scarring this procedure is still not widely accepted. This study presents the long-term results of percutaneous tennis elbow release in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
1
16
1
Order By: Relevance
“…Nazar et al have also shown that percutaneous release significantly improves Oxford elbow score in the patients with tennis elbow. 8 They also found postoperative Oxford elbow score was 42.8 whereas it was 35.87 in our study.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Nazar et al have also shown that percutaneous release significantly improves Oxford elbow score in the patients with tennis elbow. 8 They also found postoperative Oxford elbow score was 42.8 whereas it was 35.87 in our study.…”
Section: Discussioncontrasting
confidence: 43%
“…Nazar et al 8 presented the long-term results of percutaneous tennis elbow release in patients when conservative measures including local steroid injections failed to relieve the symptoms. They found that the postoperative outcome was good to excellent in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…46-48 Percutaneous release may be performed in the office setting with the patient conscious. However, it generally precludes reconstruction after debridement.…”
Section: Treatmentmentioning
confidence: 99%
“…A recent study reached the same conclusion but there were no preoperative data of the patients [18].…”
Section: Discussionmentioning
confidence: 83%